Designing the Tourist and Recreational Image of the Territory. The Example of the Zaryadye Park - EVSTRATOVA, Tatiana Anatolyevna; KABANOVA, Elena Evgen'evna; VETROVA, Ekaterina Alexandrovna; KATAEVA, Valentina Ivanovna (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019, 2020)
The state autonomous cultural institution of the Moscow "Zaryadye Park" is the first park constructed in borders of the Boulevard ring, the new cultural driver of Moscow, a key link in network of walking routes around the Kremlin. The park was conceived as the platform for dialogue about story, natural wealth of Russia, science, art, about the future of Moscow and the country in general. The park is open for new people, the ideas and technologies and encourages interest in knowledge and innovations. Unlike other Moscow parks having extensive territories for the organization of recreational activity, Zaryadye has a number of features which form its originality: the small territory, multilevelness, the botanical collection showing the natural variety of Russia, media complexes which do not have analogs in Moscow, a wide range of scientific and educational programs. In the Zaryadye park for visitors various information booths are presented; media complexes; tourist information centers; showrooms; shops of souvenirs and gifts; cafe and bars; "Ice cave"; florarium; scientific and informative center "Reserved Embassy"; big amphitheater; concert hall; modern gastronomic food court. The majority of exhibitions and actions in the park are devoted to natural wealth of Russia. Expositions mention, generally land world. In the Zaryadye Park there are practically no objects acquainting visitors with the richest water resources of our country. Construction and development of an oceanarium are one of the most perspective and favorable directions of large business. Having appeared relatively recently, the oceanarium industry literally blew up the sphere of entertainments and quickly rose by business Olympus top. The world practice visually confirms high profitability of projects of construction of oceanariums. More and more oceanariums are under construction worldwide – each of them shows excellent indicators of payback. Our country after the western and east neighbors joined in "oceanarium" process, but trends of the last year’s show: Russia will become in one row already soon with the countries in the territory of which the greatest number of the best oceanariums with a world name is constructed. That it happened as soon as possible, it is necessary to combine efforts of people which have a desire and opportunities to realize grandiose projects of construction of oceanariums.